Crime, policing and punishment in England, 1660-1914 - Gray, Drew D. (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
Acknowledgements -- Key themes in the history of crime -- Introduction: methods, themes and debates in the history of crime -- Media and crime -- Violence : the decline of homicide and a growing intolerance towards assault -- The nature of property crime -- The causes of property crime -- Gender & crime in the criminal justice system : women as victims -- Gender & crime: women as perpetrators of crime -- Juvenile crime : from artful dodger to reformatory boy -- The evolution & development of the English criminal justice system -- From parlour to police court : the role of the JP and the emergence of the modern magistrate -- Dogberry to detectives : policing from amateurs to professionals -- Removing the victim? : the changing nature of prosecution in the courts in England -- The decline and fall of the "bloody code" : the changing nature of punishment policy in the long eighteenth century -- The rise and fall of incarceration -- Conclusions and suggestions for future research -- Bibliography -- Index